Phylogeography and demographic history of the cyprinid fish Barbodes semifasciolatus: implications for the history of landform changes in south mainland China, Hainan and Taiwan - Wang, Junjie; Wu, JinXian; Yang, Jinquan; Chen, Jiabo; Yang, Jiemei; Li, Chao; Lin, Hung-Du; Zhao, Jun (Frontiers in Ecology and Evolution, 2023)
Hainan Island and Taiwan Island are adjacent to the southern margin of mainland China and Vietnam. During glacial periods, global sea levels dropped, allowingindicating that the land bridges connected the continental island and mainland, connecting rivers and providing dispersal opportunities that shaped the origin and diversification of freshwater fishes.connecting rivers and providing dispersal opportunities for understanding the origin and diversification of freshwater fishes. Barbodes semifasciolatus is distributed in various water systems of Vietnam, Hainan, Taiwan, and southern mainland China and is restricted to the southern region of the Min River. Our study aimed to evaluate the genetic diversity and phylogeography of B. semifasciolatus using the mtDNA cyt b gene (1,141 bp). A total of 107 haplotypes were identified from 395 specimens in twenty-three populations, and high haplotype diversity (1.000) and low nucleotide diversity (0.0134) were detected. Mitochondrial phylogenetic analysis and haplotype network analyses revealed three major lineages according to geographical distribution. Lineage A was mainly distributed in Hainan Island, Vietnam and the southern region of the Pearl River in mainland China. Lineage B was distributed only in southeastern Hainan Island. Lineage C was distributed in the coastal rivers of mainland China and Taiwan. We suggest that the river in the Guangdong region is a colonization route in South Taiwan and that the populations distributed in the Pearl River region moved southward to Hainan Island and Vietnam based on the network and Bayesian binary MCMC (BBM) analysis. Our This is a provisional file, not the final typeset article demographic history results indicated that the populations of B. semifasciolatus experienced a bottleneck event following a recent population expansion (DECINC model) supported by ABC analysis. We suggest that sea-level changes exerted pronounced effects on the demography of B. semifasciolatus on the continental island and in the mainland during the late Pleistocene glacial cycles.